ANALISIS PROSES PEMURNIAN AIR TANAH PADA DEPOT AIR MINUM UNTUK MENJAMIN KUALITAS AIR LAYAK KONSUMSI DI DAERAH PERKOTAAN - Ananda Zulmi; Arham Wahyudi; M.Nur Tondi; Novan Wicaksana; Sari Wulandari (Nirta Learning Centre, 2025)
The need for clean water in urban areas is increasingly pressing due to limited water distribution from PDAMs and the high cost of bottled water. Refillable drinking water depots present an alternative solution, but raise concerns regarding the quality and safety of the water produced. This study aims to analyse the groundwater purification process at drinking water depots in Sidorejo Hilir urban village, Medan, to ensure the quality of water suitable for consumption. The method used was a qualitative approach with a case study, using interviews, observation, and documentation as data collection techniques. The results showed that raw water comes from a borehole and is processed through six stages of filtration, from filtration using special sand to sterilisation with ultraviolet light. Water containers are also disinfected before filling. However, laboratory testing found that all depot water samples still contained coliform bacteria, posing a potential health risk. This study recommends stricter supervision of depot sanitation as well as periodic water quality tests so that health standards can be met.